Blue Ridge Folklife. - Olson, Ted (University Press of Mississippi, 1998)
In the years immediately preceding the founding of the American nation the Blue Ridge region, which stretches through large sections of Virginia and North Carolina and parts of surrounding states along the Appalachian chain, was the American frontier. In colonial times, it was settled by hardy, independent people from several cultural backgrounds that did not fit with the English-dominated society. The landless, the restless, and the rootless followed Daniel Boone, the most famous of the settlers, and pushed the frontier westward. The settlers who did not migrate to new lands became geographic.